2016
DOI: 10.1007/s40123-016-0056-4
|View full text |Cite
|
Sign up to set email alerts
|

Primary Baerveldt Shunt Implantation: Outcomes and Complications

Abstract: IntroductionThis study is a retrospective case series to evaluate the outcomes and complications of Baerveldt glaucoma implant surgery (BGI) in patients without prior cataract or incisional glaucoma surgery.MethodsPatients who underwent 350-mm2 BGI through the Glaucoma Service of the University of Illinois at Chicago between 2010 and 2015 were included in this study. Outcome measures included age, sex, ethnicity, operated eye, preoperative diagnosis, preoperative, and sequential postoperative intraocular press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
(45 reference statements)
1
4
0
Order By: Relevance
“…In the metaanalysis, based on eight studies, the overall effect size indicated that glaucoma surgery significantly reduces the progression velocity in glaucoma. Several studies reported an unchanged BCVA after glaucoma surgery, for both TE (Bevin et al 2008;Bhardwaj et al 2013;Balekudaru et al 2014;Bertrand et al 2014;Iverson et al 2016) and BGI (Namavari et al 2016), and in a recent randomized clinical trial (RCT) comparing primary BGI with TE (Islamaj et al 2018). This is in agreement with our results.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the metaanalysis, based on eight studies, the overall effect size indicated that glaucoma surgery significantly reduces the progression velocity in glaucoma. Several studies reported an unchanged BCVA after glaucoma surgery, for both TE (Bevin et al 2008;Bhardwaj et al 2013;Balekudaru et al 2014;Bertrand et al 2014;Iverson et al 2016) and BGI (Namavari et al 2016), and in a recent randomized clinical trial (RCT) comparing primary BGI with TE (Islamaj et al 2018). This is in agreement with our results.…”
Section: Discussionsupporting
confidence: 93%
“…) and BGI (Namavari et al. ), and in a recent randomized clinical trial (RCT) comparing primary BGI with TE (Islamaj et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…tubes as primary choice). 14 , 15 Considering the cost-effectiveness rationale, trabeculectomy remains the most frequent surgical procedure in glaucoma. 16 …”
Section: Introductionmentioning
confidence: 99%
“…tubes as primary choice). 14,15 Considering the cost-effectiveness rationale, trabeculectomy remains the most frequent surgical procedure in glaucoma. 16 After primary trabeculectomy performed in different types of glaucoma, multiple studies reported variable longterm success rates (between 48 -98%), depending on definition and time-to-failure calculations, 17 but fewer studies reported results after trabeculectomy in advanced glaucoma only.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported an unchanged BCVA after glaucoma surgery, for both TE (Balekudaru et al 2014, Bertrand et al 2014, Bevin et al 2008, Bhardwaj et al 2013, Iverson et al 2016 and BGI, (Namavari et al 2016) and in a recent randomized clinical trial (RCT) comparing primary BGI with TE. (Islamaj et al 2018) -25.3[3.5] dB) who underwent a TE, that nine of 104 patients lost two lines of Snellen or more -deemed to be related to glaucoma -at the end of the follow-up (i.e., on average three years postoperatively).…”
Section: Discussionmentioning
confidence: 99%